An organ‐specific transcriptome atlas of Curcuma wenyujin: MicroRNAs, phasiRNAs, and metabolic pathways - Xiaoxia Ma; Yinju Tang; Zedi Feng; Xiu Yin; Yijun Meng; Xiaopu Yin; Tian Xie (The Plant Genome)
Abstract Curcuma wenyujin Y. H. Chen et C. Ling (C. wenyujin) is a medicinal plant widely used for clinical treatments. In this study, integrated omics data analyses enabled us to discover the microRNAs (miRNAs) and the phased small interfering RNAs (phasiRNAs) on a transcriptome‐wide scale. A total of 186 mature miRNAs and 23 precursors were reported. Besides, 31 miRNAs of 14 families were organ‐specifically expressed, and 13 of these miRNAs could perform organ‐specific target regulation. More than 80% of the phasiRNA loci were organ‐specifically expressed, especially in tubers. In some cases, phasiRNAs with distinct increments, but with accordant organ‐specific expression patterns, were generated from a highly overlapped region, indicating that different machineries might be synchronously engaged in phasiRNA processing. Based on the transcriptome assembly, 28 and 56 tuber‐specific genes were identified to be involved in alkaloid and terpenoid metabolisms, respectively. Analysis of the enzyme‐coding genes of the β‐elemene biosynthetic pathway showed that the downstream genes were tuber‐specific, while the upstream genes were not. We assumed that the precursor metabolites produced in the other organs might be delivered to the tubers for the final steps of β‐elemene biosynthesis. Summarily, our report provided an organ‐specific transcriptome atlas of C. wenyujin, which could serve as the basis for the molecular studies on organ development and secondary metabolisms in this plant.